STUDENT WORKSHEETS ON INTEGERS AND FRACTIONS BASED ON OPEN-ENDED APPROACH - Sitti Zuhaerah Thalhah; Aulia Manda; Muhammad Hajarul Aswad; Sitti Busyrah Muchsin; Mufidapuspadina (JF Publisher, 2023)
This research aims to determine the validity, practicality, and effectiveness of student worksheets in learning mathematics on integers and fractions based on open-ended approach. This type of research is Research and Development (R & D) research using the ADDIE model. Students of seventh grade of SMPN 1 Bua Ponrang were the subjects of this research. The instruments used are validation sheets for material experts, media and design experts, then practicality questionnaires for teachers and students. The data analysis technique used is descriptive qualitative and descriptive quantitative data analysis. The assessment results based on the first material expert validation questionnaire obtained a score of 78.94% which means